An innovation procurement clinical framework: A qualitative study. Issue 1 (January 2021) - Coderre-Ball, Angela M.; Dalgarno, Nancy; Baumhour, Jessica; Zubani, Vittoria; Ko, Iris; van Wylick, Richard; Fitzpatrick, Michael
Innovation Procurement Strategies (IPS) strive for purchasing healthcare solutions that do not yet exist on the market and are increasingly being advocated to improve health outcomes while managing escalating healthcare costs. Due to the newness of IPS, there are limited resources available to healthcare organizations and professionals looking to engage in IPS. The purpose of this study was to develop an evidence-based clinical framework to guide healthcare organizations and professionals. Adopting a qualitative grounded theory approach, we interviewed participants with experience in innovation procurement to understand the skills, resources, and supports needed to initiate and oversee an IPS project. Using thematic design and open coding, three overarching themes emerged from the data and formed the basis of our IPS clinical framework. By describing the components, skills, and supports and resources necessary for engaging in IPS, our framework addresses the knowledge gap in healthcare organizations and professionals wishing to implement IPS.